Recognition and freedom : Axel Honneth's political thought - Jakobsen, Jonas.; Lysaker, Odin, 1976- (Social and Critical Theory, 2015)
Recognition and Freedom brings together leading international scholars to discuss the political thought of the social philosopher Axel Honneth. In addition to providing an introduction to Honneth's political thought, the book examines topics such as education, solidarity, multiculturalism, agonism, neo-liberalism and the ways in which these issues challenge core aspects of liberal democracies. The book includes an interview with Axel Honneth in the light of his most recent work, Freedom's Right, as well as an essay by him previously unpublished in English.